Fusion insights from ultrasonic and thermographic inspections for impact damage analysis - Torbali, Muhammet E.; Alhammad, Muflih; Zolotas, Argyrios; Avdelidis, Nicolas P.; Ibarra-Castanedo, Clemente; Maldague, Xavier P. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Low energy impact damage in composite materials may be more concerning than it appears visually, often requiring a detailed examination for accurate assessment to ensure safe and sustainable operation. Non-destructive testing (NDT) methods provide such inspection techniques, and in this paper, NDT-based fusion is explored for enhanced identification of defect size and location compared to indepdently using individual NDT methods separately. Three Carbon Fiber Reinforced Polymer (CFRP) specimens are examined, each with an impact damage of a given energy level, using pulsed thermography (PT) and phased array (PA) ultrasonic methods. Following the extraction of binary defect shapes from source images, a decision-level fusion approach is performed. The results indicate that combining ultrasonic and infrared thermography (IRT) inspections for CFRP composite materials is promising to achieve enhanced and improved detection traceability.